PREDICTORS OF ACUTE OTITIS MEDIA SEVERE COURSE IN CHILDREN AND HEAT SHOCK PROTEIN GENE HSP70-2 (RS1061581) TRANSCRIPTION ACTIVITY - Sydorchyk, Larysa; Sakovets, Oleksii (Eastern Ukrainian Medical Journal, 2026)
Introduction. Acute otitis media (AOM) is one of the most common pediatric health issues worldwide. Despite extensive research on the AOM causes, there is no enough evidence of molecular-genetic and clinical progression risk-factors of AOM severe course. Objectives: to assess predictors of AOM severe course in children and the heat-shock protein gene (HSP70-2; rs1061581) impact, as well as its transcriptional activity. Materials and Methods. A prospective cohort study involved 95 children with AOM, aged from 7 to 18 years old. Among the examined children were 34.74% (n=33) girls and 65.26% (n=62) – boys. Children were divided by age (12–18 yo/7–11 years), AOM severity (non‑severe/severe), nature of the mucous membrane inflammation (purulent/catarrhal). The control group included 50 practically healthy children: 30 boys (60.0%), 20 girls (40.0%). The groups did not differ by age (p>0.05). HSP70-2 (rs1061581) gene genotyping was performed by qPCR method. HSP70-2 gene transcriptional activity analyzed by eQTL in the open GWAS database. Risk assessed by Risk Ratio, Odds Ratio and 95% Confidence Interval. Results. The risk of a more severe clinical course of AOM elevates with eardrum perforation and otorrhea almost 15 and 10 times (OR 95%CI: 3.17–69.39 and OR 95%CI: 3.51–30.60; p<0.001), severe otalgia and purulent ear discharge – more than 20 and 18 times (OR 95%CI: 6.76–62.96 and OR 95%CI: 6.54–51.59; p<0.001), mainly with unilateral otitis localization – more than 2 times (OR 95%CI: 0.98–4.99; p=0.055) and otitis at pre-pubertal age (7–11 years) – more than 6 times (OR 95%CI: 1.29–29.24; p=0.01), respectively. The appearance of purulent discharge from the ear at the age of 7–11 years enhances the severe AOM likelihood more than 7 times (OR=7.29; OR 95%CI: 1.44–37.01; p=0.045). Moreover, the AOM risk increases in A-allele carriers of the HSP70-2 gene (rs1061581) almost twice (OR=1.76; OR 95%CI: 1.02–3.05; p=0.026). Expression quantitative trait loci of the HSP70-2 gene (rs1061581) were identified in 29 tissues and organs. The HSP70-2 gene increases the transcriptional activity of the following genes: HSP70-2 (rs11576014) (β≥0.914; p=2x10-6), HSP70-1 (rs17201192/rs2763977/rs9469058) (β≥0.029–0.67; p<2x10-10); SNHG32 (rs7769158/rs7765136) (β≥0.15–0.30; p<9x10-18). The HSP70-2 gene causes transcriptional repression of the following genes: HSP70-1 (rs2763979/rs2763979/rs1265947) (β≤0.09; p<6x10-6) and SNHG32 (rs3115674/rs35592410/rs3130476/rs34278010/rs2471980) (β≤0.09; p<2x10-7). Conclusions. Predictors of AOM severe course are otorrhea, purulent ear discharge, severe otalgia, perforation of the eardrum, otitis in children 7–11 years old, and the A-allele of the HSP70-2 gene (rs1061581).